Species composition, utilization pattern, and socioeconomics of Chakma community home gardens in the southwestern part of Mizoram - C.Z. , Lalhmachhuani; Angom, Aruna Devi; Upadhyaya, Kalidas (Indian Journal of Agroforestry, 2026)
The present study documented the species composition, utilization patterns, and socioeconomics of Chakma community home gardens in Mizoram. A total of 44 different species were identified in the studied area, of which 23 were trees, 3 were shrubs, and 18 were herb species belonging to 12 genera and 25 families. This distribution showed a relative prevalence of 52.27% for trees, 6.82% for shrubs, and 40.9% for herbs. The studied home gardens exhibited complex structure, both vertically and horizontally. Five vertical strata (emergent, canopy, understorey, shrub, and herb) were identified, with the highest percentage of species in the emergent stratum, 29.55%, followed by 13.64% in the canopy layer, 9.09% in the sub-canopy layer, 6.82% in the shrub layer, and 40.91% in the herb layer. Cultivated food crops and medicinal plants constituted 24.24% of the 50 surveyed gardens. About 21.21% constituted fruit trees in the studied homegardens. Timber and fuel wood species constituted 9.09% and 7.57%, respectively. Others (i.e., species which are used as fodder, charcoal, oil, etc.) constituted 13.63%. the net income from home garden productivity ranged from Rs 113586 to Rs 174511. These homegardens contribute significantly towards livelihood of Chakma community in the study area by catering subsistence needs of daily household needs and also supports agriculture in case of exigencies through diversified income. Choice of superior species with high market value, use of proper planting arrangement, use of high yielding varieties of crops, proper management of woody species, crop protection measures, proper post harvesting equipments, value addition of products and improved marketing and transportation facilities are some of the measures so as to make the existing homegardens highly productive and sustainable.